THE IMPACT OF INFRASTRUCTURE ON LEARNING OUTCOMES: SURVEY STUDY AT HARVARD MIDDLE SCHOOL - Pitriani, Pitriani; Nahuda, Nahuda; Nadiah, Nadiah (Spektra: Jurnal Ilmu-ilmu Sosial, 2025)
This research is motivated by the fact that one of the factors that can improve student learning outcomes is complete and adequate infrastructure. Infrastructure facilitates and facilitates student learning in the learning process, thus facilitating optimal learning outcomes. This study aimed to determine the effect of infrastructure on improving learning outcomes at Harvard Junior High School, Jakarta. The method used in this study was correlation with a quantitative approach. Simple random sampling was used, with 27 students as respondents. The results showed that the Product Moment coefficient test yielded an "rxy" or "ro" of 0.232, while "rt" at the 5% significance level was 0.388 and at the 1% significance level was 0.496. Therefore, the null hypothesis (Ho) was accepted, while the null hypothesis (Ho) was rejected. Based on these results, it can be concluded that infrastructure does influence learning outcomes.